Synthesis of an Amphiphilic Bis‐Aqua Gd(OBETA) Complex for the Preparation of High‐Relaxivity Supramolecular Magnetic Resonance Imaging Probes1. Issue 2 (17th September 2015) - Negri, Roberto; Carniato, Fabio; Botta, Mauro; Giovenzana, Giovanni B.; Tei, Lorenzo
Abstract: Prompted by the favourable relaxometric, thermodynamic and kinetic properties of the bis‐hydrated Gd(OBETA) (OBETA=2, 2′‐oxybis(ethylamine)‐ N, N, N ′, N ′‐tetraacetic acid) complex, a novel derivative tailored with an n ‐hexadecyl chain was synthesised. The amphiphilic gadolinium complex was designed and prepared with the aim of obtaining high relaxivity supramolecular aggregates by self‐assembly in micelles and liposomes. Thus, lipidic nanoparticles were prepared and characterised by dynamic light scattering and 1 H NMR relaxometry. Relaxivity values of up to 48.3 mm −1  s −1 (20 MHz and 298 K) were registered in liposomal aggregates. The binding to human serum albumin (HSA), evaluated both in terms of affinity and relaxometric properties of the supramolecular adduct, yielded exceptionally high relaxivity values (71.4 mm −1  s −1 at 30 MHz and 298 K). Abstract : Amphiphiles assemble : The synthesis of a new amphiphilic Gd‐OBETA‐like complex (see structure) and its ability to form micellar aggregates that can be incorporated in the bilayer of liposomes and that interact with human serum albumin (HSA) are reported. 1 H NMR relaxometric studies on these supramolecular adducts demonstrate the potential of the new amphiphilic chelates for the attainment of high relaxivity systems.